Rate-Dependent Mechanics of Superplastic Processes - Ragab, Abdel-Rahman A.F. (My University, 1973)
Superplasticity is a hot-working phenomenon exhibited by many metallic alloys and observed above a temperature of about 40% of the absolute melting point. It is characterized by an ultra-fine grain microstructure, an unusually high rate dependence and very low resistance to deformation at low strain rates.
The plasticity theories and constitutive equations used in the analysis of secondary creep in structures are shown to be formally applicable to the study of superplastic deformation. A non-linear viscous model, with certain limitations, is employed to analyze superplastic deformation problems.
This thesis presents three separate and independent pieces of work. These problems namely; (a) analysis of post-necking geometry in tensile-forming processes, (b) creep testing of superplastic material in sheet form and (c) reverse-extrusion of rate-dependent materials, represent in the author's opinion three most important problems relating to the use of superplastic alloys in industry.
In tensile forming processes of superplastic alloys the deformation is unstable and it is shown that geometric non-uniformities develop continuously. The features of such deformation system are illustrated by the numerical analysis of initially non-uniform, tensile bars and thin-walled tubes expanded by internal pressure. Experimental results obtained from testing zinc-aluminum alloy are compared with the numerical results and satisfactory correlation is observed.
A technique is presented for obtaining creep data for superplastic sheets using a test in which a strip or indeed the whole sheet is arranged as a cantilever loaded by its own weight. Theory is given for deriving stationary creep parameters from measured deflection rates and for determining a stress, strain-rate curve using the skeletal point method. Tensile and bending creep tests were performed on superplastic zinc-aluminum sheets at room temperature and the creep data from both types of tests are compared.
In bulk forming of rate-dependent materials the load requirement are highly dependent on the forming speed. In the present work the traditional analytical method of slip-line field analysis has been extended to accommodate the extrusion of rate-sensitive materials such as superplastic alloys. The volume of the deformation zone and the effective mean strain-rate identified by the slip-line field solutions were incorporated to define a geometric factor which permits the extrusion pressure to be determined for a non-linear viscous material. Experimental results on reverse-extrusion of both as-cast and superplastic zinc-aluminum agree well with theoretical analysis.
Keywords: Mechanical Engineering; Mechanical Engineering